Computerized Symbol Digit Modalities Test in a Swiss Pediatric Cohort Part 1: Validation - Hochstrasser, Céline; Rieder, Sarah; Jufer-Riedi, Ursina; Klein, Marie-Noëlle; Feinstein, Anthony; Banwell, Brenda L.; Steiner, Michelle; Cao, Li Mei; Lidzba, Karen; Bigi, Sandra (Frontiers in Psychology, 2021)
Objective: The objective of this study was to evaluate the computerized Symbol Digit Modalities Test (c-SDMT) in a Swiss pediatric cohort and to establish a comparability of norms by observing sex effects, age-effects, and test–retest reliability in comparison to values obtained for the paper and pencil version of the Symbol Digit Modalities Test (SDMT). Methods: This longitudinal observational study was conducted in a single-center setting at the University Children's Hospital of Bern. Our cohort consisted of 86 children (45 male and 41 female) aged from 8 to 16 years. The cohort included both healthy participants (n = 38) and patients (n = 48) hospitalized for a non-neurological disease. Fortyeight participants were assessed during two testing sessions with the SDMT and the c-SDMT. Results: Test–retest reliability was high in both tests (SDMT: ICC = 0.89, c-SDMT: ICC = 0.90). A reliable change index was calculated for the SDMT (RCIp = −3.18, 14.01) and the c-SDMT (RCIp = −5.45, 1.46) corrected for practice effects. While a significant age effect on information processing speed was observed, no such effect was found for sex. When data on the c-SDMT performance of the Swiss cohort was compared with that from a Canadian cohort, no significant difference was found for the mean time per trial in any age group. Norm values for age groups between 8 and 16 years in the Swiss cohort were established. Conclusions: Norms for the c-SDMT between the Swiss and the Canadian cohort were comparable. The c-SDMT is a valid alternative to the SDMT. It is a feasible and easy to administer bedside tool due to high reliability and the lack of motor demands.